EFFECT OF VARIOUS CONCENTRATION ON PHYSICAL PARAMETER OF FEMININE HYGIENE SWEET BASIL LEAF EXTRACT (Ocimum Basilicum) : FOAM STABILITY AND HEIGHT EVALUATION STUDIES - Fauziah, Arsy (Indonesian Journal of Cosmetics, 2025)
Sweet basil or Kemangi (Ocimum basilycum) is known not only for its distinct aroma or flavor but also its therapeutic potential. Due to phytochemical ingredients, sweet basil become promising material for cosmetics and personal care industries such as feminime hygiene. This study aims to investigate the effect of varying concentration on foam stability from sweet basil leaf extract feminine hygiene. The extract was formulated into feminime hygiene with varying concentrations from 20%, 25%, 30%, 35% and 40%. Each formulas were evaluated on height evaluations and foam stability, analyze with Kruskal-Wallis test and Mann-Whitney test, respectively. The results was statistically significant for each parameters between formula I (20%) and formula III (30%).